CdX2 Coordination Polymers with 2‐Chloropyrazine and 2‐Methylpyrazine: Similar Ligands – Similar Structures – Different Reactivity. Issue 9 (3rd March 2017) - Näther, Christian; Jess, Inke; Germann, Luzia S.; Dinnebier, Robert E.; Braun, Michael; Terraschke, Huayna
Abstract : Several coordination compounds, based on Cd halides and 2‐methylpyrazine (Mepyz) or 2‐chloropyrazine (Clpyz) as N‐donor coligands, are synthesized and their crystal structures determined by either single‐crystal or X‐ray powder diffraction (XRPD). In [CdX2 (2‐Clpyz)2 ] n (X = Cl:1 ‐Cl‐Clpyz; X = Br:1 ‐Br‐Clpyz; and X = I:1 ‐I‐Clpyz) and [CdX2 (2‐Mepyz)2 ] n (X = Cl:1 ‐Cl‐Mepyz; X = Br:1 ‐Br‐Mepyz; and X = I:1 ‐I‐Mepyz), the Cd cations are octahedrally coordinated by two N‐donor ligands and are linked into chains by the halide anions that share common edges. In the ligand‐deficient compounds [CdX2 (2‐methylpyrazine)] n (X = Cl:2 ‐Cl‐Mepyz; X = Br:2 ‐Br‐Mepyz; and X = I:2 ‐I‐Mepyz), similar CdX2 chains, which are connected into layers by the N‐donor ligands, are observed. Thermal analysis of all1 ‐Mepyz compounds shows a transformation into2 ‐Mepyz, which is not observed for the 2‐chloropyrazine compounds. On further heating, compounds of composition [(CdX2 )2 (2‐Mepyz)] n (X = Cl:3 ‐Cl‐Mepyz; X = Br:3 ‐Br‐Mepyz) and [(CdI2 )3 (2‐Mepyz)2 ] (4 ‐I‐Mepyz) are observed. A discrete complex, with the composition CdI2 (2‐Mepyz)2 monohydrate (1 ‐I‐Mepyz‐H2 O), and a hydrate with the composition [(CdI2 )(2‐Mepyz)]· 1.5H2 O (2 ‐I‐Mepyz‐H2 O) with an unknown structure, were also synthesized. Both lose the water molecules upon heating. Luminescence measurements show blue to orange emissions in the range of ca. 22530–16276 cm –1, depending on the halide or pyrazine substituent, as well as the metal halide/ligand ratio. Abstract : Reaction of CdX2 (X = Cl, Br, I) with 2‐chloro‐ and 2‐methylpyrazine leads to 1D compounds [CdX2 (L)2 ] n (L = 2‐chloro‐, 2‐methylpyrazine). The 2‐methylpyrazine compounds transform into 2D coordination polymers upon heating; this is not observed for the 2‐chloropyrazine compounds. Luminescence spectra show distinct properties, depending on the halide anions, neutral ligands and metal halide/ligand ratio.